Studi Makna Pada Onomatope《美男家族》Měinán Jiāzú dalam Aplikasi Webtoon - Zianty Feblita; Tri Wahyu Retno Ningsih; Deasy Anastasia Putri (Universitas Pendidikan Indonesia, 2023)
This research has a purpose to analyze the form and meaning of onomatopoeia in the Webtoon《美男家族》Měinán Jiāzú. The research data used in this study uses textual data taken from Webtoon《美男家族》Měinán Jiāzú. The research used qualitative descriptive method. In this research used theory from Enckell and Rézeau (2005) and Yin Binyong (1990). The results of this research showed that, there were 39 data of onomatopoeia form according to Enckell and Rézeau including 22 onomatopoeias of human sound, 9 onomatopoeias of good sound, 3 onomatopoeias of natural sound, 2 onomatopoeias of sound variation, and 3 onomatopoeias of sound abstraction. While the data of onomatopoeia form according to Yin Binyong theory, it contains 24 simple forms of which 16 of them are monosyllable simple forms, 2 simple forms of alliterative disyllable, 1 simple form of vowel rhymed, and 5 other simple forms. In addition, there are 15 onomatopoeias of reduplicated form containing 5 AA form, 7 AAA form, 2 ABB form, and 1 ABAB form.